2018
DOI: 10.1007/s10344-018-1227-5
|View full text |Cite
|
Sign up to set email alerts
|

Associations between duck harvest, hunting wing ratios and measures of reproductive output in Northern Europe

Abstract: Ducks are important game species, hunted in several countries throughout their annual cycle. We investigated whether the size of the annual duck harvest in Finland and Denmark reflected annual reproductive output in three common quarry duck species. Finland represents an important breeding area and Denmark important staging/wintering grounds for common teal (Anas crecca), Eurasian wigeon (Mareca penelope) and common goldeneye (Bucephala clangula). We assessed whether (i) annual duck harvest in these two countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Earlier studies have shown a strong correlation between national harvest estimates and population size for bird species with open hunting season and without bag limits (Cattadori et al 2003). Even though such a relationship is typically less clear in migratory species (Holopainen et al 2018) we expected similar patterns for Canada and greylag goose in our study. One explanation for the contrast between the two species may be that the effectiveness of hunters can reach a plateau resulting in stable harvest numbers not corresponding to a continued population growth (as described for lesser snow goose; Johnson et al 2012).…”
Section: Discussionsupporting
confidence: 75%
“…Earlier studies have shown a strong correlation between national harvest estimates and population size for bird species with open hunting season and without bag limits (Cattadori et al 2003). Even though such a relationship is typically less clear in migratory species (Holopainen et al 2018) we expected similar patterns for Canada and greylag goose in our study. One explanation for the contrast between the two species may be that the effectiveness of hunters can reach a plateau resulting in stable harvest numbers not corresponding to a continued population growth (as described for lesser snow goose; Johnson et al 2012).…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, the juvenile proportion of hunters' returns is probably representative of the population. Long-tailed duck juveniles resemble www.nature.com/scientificreports/ mature females in autumn and winter so hunting pressure is unlikely to be age dependent, as for some other quarry species 92 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, juvenile proportion of hunters' returns is probably representative of the population. Long-tailed duck juveniles resemble mature females in autumn and winter so hunting pressure is unlikely to be age dependent, as for some other quarry species 91 .…”
Section: Discussionmentioning
confidence: 99%